Continuous cultivation of Chlorella minutissima 26a in landfill leachate-based medium using concentric tube airlift photobioreactor - Tagliaferro, Geronimo Virginio; Izario Filho, Helcio Jose; Chandel, Anuj Kumar; Silva, Silvio Silverio da; Silva, Messias Borges [UNESP]; Santos, Julio Cesar dos (Elsevier B.V., 2019)
The use of landfill leachate was studied as nutrient source for Chlorella minutissima 26a microalgae in mixotrophic cultivation in a continuous concentric tube airlift photobioreactor, concomitantly promoting the leachate bioremediation. Medium was composed of leachate, water and sodium chloride and the cultivation process was performed in continuous mode under fluorescent light with a photon flux of 80-90 mu mol m(-2) s(-1). The effects of different leachate concentrations were evaluated for the microalgal growth, biomass composition (lipid, carbohydrate, protein and ash) and for the removal of organic compounds, nitrate and metals from the medium. Increase in leachate concentration from 5 to 10% in the medium, caused the reduction in the lipid amount but increased the carbohydrate amount with no marked effect on the protein content. In the steady state, the maximum productivity of biomass, lipids, carbohydrates and proteins were 232.0 +/- 7.6 (7.5% of leachate concentration), 96.6 +/- 7.8 (5% of leachate concentration), 33.4 +/- 2.1 (10% of leachate concentration) and 47.1 +/- 3.0 mg L-1 d(-1)(7.5% of leachate concentration), respectively. Maximum values obtained for the reduction in chemical oxygen demand, removal of total organic compounds and inorganic nitrate from the landfill leachate during cultivation in steady state were 92.8% (7.5% of leachate concentration), 90.5% (7.5% of leachate concentration) and 100% (5% of leachate concentration), respectively. Maximum values of removal of metals from the medium were 63%, 72%, 100%, and 67% for Cr, Fe, Al and Ba, respectively. These results indicated that the use of the landfill leachate could be a possible source for the sustainable production of microalgal biomass, also resulting in concomitant removal of undesirable components, i.e. organics and metals.
Keywords: Chlorella minutissima; Lipids production; Carbohydrates production; Landfill leachate; Bioremediation